PENGGUNAAN SCAFFOLDING UNTUK MEMPERBAIKI KESALAHAN SISWA SMP DALAM MENYELESAIKAN MASALAH MATEMATIKA - Susilo, Claudya Zahrani (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2019)
AbstractThis research is a qualitative description research which describe scaffolding to fix the juniorhigh students' error in solving mathematics problem. The research subject is 7th grade studentwhich represent mathematics ability in high, medium and low level. The result shows that thestudents' problem are (1) error in writing information of the problem, (2) error in writing theformula that is used in solving problem, and (3) komputational error. Scaffolding is used to fixthe students' problem. Those are (1) asking students to reread the problem, (2) givingdirectional question to students, (3)asking students to reflect their answer,and (4) askingstudents to recheck the result of their problem. Keywords: scaffolding, error, mathematics' problem